Increase the Attractiveness of Local Fruits to the Buying Intention of Hedonic Consumers in Bali - Korry, Putu Dyah Permatha; Yulianti, Ni Made Dhian Rani; Yunita, Putu Irma (International Research Journal of Management, IT & Social Sciences, 2017)
In order to improve the competitiveness of local fruits in Bali in particular and Indonesia in general against imported fruits, especially for hedonic consumers, appropriate strategies and policies are needed in the development and strengthening of the market. So the purpose of this research was: 1). To know the influence of labeling to the buying intention of local fruit on hedonic consumers in Bali. 2) To know the influence of brand image to consumer buying intention of local fruit on hedonic consumers in Bali. 3). To know the influence of packaging on the buying intention of local fruit on the hedonic consumer in Bali. This research was conducted on local and imported fruit consumers in Bali. The research location is in fruit shops, supermarkets and traditional markets that sell local and imported fruits in Bali Province. This data is obtained by using survey method, that is by distributing questionnaires to the respondents. Data were analyzed by using multiple linear regression analysis methods by using SPSS program version 20.0 for windows. The result of SPSS test shows that labeling has a positive and significant influence on consumer buying intention (B = 0.257; t = 3.208; p <0,05), brand image have positive and significant influence on consumer buying intention (B = 0.550; t = 8.507; p <0.05), while packaging has a positive but not significant effect on consumer buying intention (B = 0.055; t = 0.576, p <0.05), and its Adjusted R Square Value of 0.454 which means that labeling, brand image , and packaging able to explain variation of consumer buying intention variable equal to 45.4% and the rest equal to 54.6% explained by other variables outside model. These results show that Hypotheses 1 and 2 are supported, whereas hypothesis 3 is not supported. Hypothesis 3 is not supported means the packaging variable has no influence on consumer buying intention.